The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2010
DOI: 10.3329/jsr.v2i2.4056
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid Composition and Antimicrobial Activity of <i>Celtis australis</i> L. Fruits

Abstract: Methyl esters of fatty acid obtained from Celtis australis fruits were subjected to GC-MS in order to determine the identity and concentration of its constituents. Methyl oleate (25.7%), methyl palmitate (22.2%), methyl tricosanoate (13.3%), methyl lineolate (7.8%), methyl dotriacentanoate (2.6%) and methyl 14-acetylhydroxypalmitate (2.1%) were the major constituents out of total characterized composition (95.455%) of fatty acid. The ethanolic extract of fruits was used for evaluating its antimicrobial activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 1 publication
1
24
0
1
Order By: Relevance
“…These results are in agreement with our previous study which has reported the antibacterial effect of hydro-methanolic extracts of leaves and seeds of C. australis 14 , as far as various extracts from this plant against S. aureus, P. aeruginosa, E. coli and B. subtilis 16 , S. aureus and P. aeruginosa 8 , P. syringe 17 and S. aureus, L. monocytogenes, P. aeruginosa and E. coli 18 . Antifungal potential: As shown in Table 5, a significant and dose-dependent antifungal effect was obtained with all extracts tested.…”
Section: Antibacterial Potentialsupporting
confidence: 94%
“…These results are in agreement with our previous study which has reported the antibacterial effect of hydro-methanolic extracts of leaves and seeds of C. australis 14 , as far as various extracts from this plant against S. aureus, P. aeruginosa, E. coli and B. subtilis 16 , S. aureus and P. aeruginosa 8 , P. syringe 17 and S. aureus, L. monocytogenes, P. aeruginosa and E. coli 18 . Antifungal potential: As shown in Table 5, a significant and dose-dependent antifungal effect was obtained with all extracts tested.…”
Section: Antibacterial Potentialsupporting
confidence: 94%
“…This was confirmed also in the present study with leaves collected in October; in addition, comparable activities were also found for the fruit mesocarp (Table 4). Badoni et al (2010) also studied the antimicrobial activities of crude extracts from hackberry fruit and reported antibacterial activities against S. aureus, B. subtilis, P. aeruginosa, and E. coli. Although different extraction solvents were used and lower MICs were determined, the growth of S. aureus was again inhibited at lower concentrations than for P. aeruginosa.…”
Section: Antibacterial Activitymentioning
confidence: 99%
“…The temperature program for the GC was configured as follows: starting temperature 50 °C for 5 min, followed by a linear gradient 3 °C min −1 to 220 °C and held for 5 min, with a source temperature of 180 °C. Compounds identification was performed by NIST library (Badoni et al 2010).…”
Section: Gc-ms Characterization Of Blmentioning
confidence: 99%